Breast Hamartoma with Coexistent DCIS: Radiological Challenges - Lazareva, Zora; Nikolova, Sonja (My University, 2024)
This article explores the diagnostic complexity of a 53-year-old woman with palpable breast abnormalities, uncovering a dual narrative of hamartoma and coexisting ductal carcinoma in situ (DCIS). Radiological insights into these lesions highlight the challenges in accurate diagnosis. Introduction: Breast hamartomas, presenting as a "breast within a breast" on mammograms, pose diagnostic challenges. In this case, a unique scenario emerges as a breast hamartoma coexists with cancer, emphasizing the complexity faced by radiologists in such diagnostic journeys. A 53-year-old woman with palpable breast abnormalities undergoes mammography, revealing a well-circumscribed mass with a "breast within a breast" appearance, characteristic of a hamartoma. However, suspicious features of malignant microcalcification within the hamartoma suggest coexisting cancer, showcasing the intricate interplay of benign and malignant elements. Ultrasound struggles to delineate the lesion's margins due to its normal breast tissue resemblance. Mammography displays the classic "breast in breast" appearance of the hamartoma, with additional features of microcalcification raising concerns of malignancy. Integrating imaging findings with pathology is crucial in discerning the complex interplay between benign and malignant elements. The diagnostic landscape reveals a breast hamartoma on the left side, intricately intertwined with cancerous components, highlighting the challenges in discerning dual pathology within breast lesions. This case illuminates the diagnostic intricacies associated with breast lesions, showcasing the coexistence of a benign hamartoma and cancerous elements. Accurate diagnosis demands a nuanced understanding of imaging findings and collaborative efforts between radiologists and pathologists. The diagnostic journey underscores the complexity of breast lesions, where a hamartoma conceals malignant elements. Advanced imaging is crucial for navigating this intricacy, and multidisciplinary collaboration is paramount for accurate diagnosis and tailored management. Keywords: Breast hamartoma, Ductal carcinoma in situ (DCIS), Mammography.
Keywords: Breast hamartoma; Ductal carcinoma in situ (DCIS); Mammography